THE ORGANIZATION AND OPERATION OF SPECIALIZED AGRICULTURAL SCHOOLS DURING THE NAZI OCCUPATION OF UKRAINE - PEREKHREST О. G. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
The article analyzes the motives and processes of the organization and functioning of specialized agricultural education institutions in the meaning of the Nazis policy in education. It is established that to organize the vocational education for a part of the rural population colonized territories the occupants were forced by lack of human resources for economic exploitation of agriculture. It is demonstrated random and contradictory nature of measures implemented by occupants in this case. If the lower and medium agricultural schools sometimes still worked and trained professionals, the higher education institutions renewed have not really launched work. Later the occupants refused to renew the practice of agricultural higher education institutions, as already established institutions have been converted to higher agricultural school. Based on the analysis of specific source material it is stated that the renewed educational institutions have insufficient educational and material resources, lacked qualified teachers, pupils and students were forced to work most of the time in agricultural work, many of them were deported to Germany. It is noted that the plans of the Nazis were not implemented because of the time factor and, because since the summer of 1943 in terms of the Soviet troops started they were not in the organization of training. No college or faculty of university agricultural profile did not manage to make even the first graduation of specialists. Further research of this problem appropriate to do in the study of the functioning of individual education institutions.